On the Existence of Local Smooth Solutions of Systems of Nonlinear Functional Equations with Deviations Dependent on Unknown Functions - Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain conditions for the existence of a local differentiable solution of a system of nonlinear functional equations with nonlinear deviations of an argument.